Cross-Sectional Return Dispersion and Time Variation in Value and Momentum Premiums - Stivers, Chris; Sun, Licheng (Journal of Financial and Quantitative Analysis, 2010)
Abstract We find that the market’s recent cross-sectional dispersion in stock returns is positively related to the subsequent value book-to-market premium and negatively related to the subsequent momentum premium. The partial relation between return dispersion (RD) and the subsequent value and momentum premiums remains strong when controlling for macroeconomic state variables suggested by the literature. Our findings are consistent with recent theoretical insights and empirical evidence that suggest that the market’s RD may serve as a leading countercyclical state variable, that the value premium is countercyclical, and that the momentum premium is procyclical.